2017
DOI: 10.22495/cocv14i3c2art12
|View full text |Cite
|
Sign up to set email alerts
|

CEO’s experience, foreign ownership and corporate social responsibility: A case of manufacturing companies

Abstract: Corporate Social Responsibility (CSR) is a commitment of the company or the business world to participate in the development of sustainable economy. It concerns companies’ social responsibilities as well as stresses the balance of economic, social, and environmental aspects. This research aims to analyze the influence of CEO’s international work experiences, foreign ownership and controlled variables of profitability and firm size on CSR disclosure. The sample of this research is represented by 134 manufacturi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 24 publications
0
14
1
1
Order By: Relevance
“…Additionally, Haniffa and Cooke (2005) suggest considering the values, motives and choices of those involved in CSR-related decisions within the company. Extant literature also supports this line of argument (Amran and Devi, 2008, Said et al, 2009, Meutia et al, 2017, Swandari and Sadikin, 2016, and Cahyani and Suryaningsih, 2016 who found foreign ownership has no significant influence on CSR.…”
Section: Foreign Ownership and Firm Social Performancementioning
confidence: 73%
See 2 more Smart Citations
“…Additionally, Haniffa and Cooke (2005) suggest considering the values, motives and choices of those involved in CSR-related decisions within the company. Extant literature also supports this line of argument (Amran and Devi, 2008, Said et al, 2009, Meutia et al, 2017, Swandari and Sadikin, 2016, and Cahyani and Suryaningsih, 2016 who found foreign ownership has no significant influence on CSR.…”
Section: Foreign Ownership and Firm Social Performancementioning
confidence: 73%
“…Therefore, compared to Arab investors, non-Arab foreign investors are expected to be more familiar with social and environmental issues and have greater emphasis on CSR in their home countries. The lack of understanding of the importance of CSR activities and the potential benefits of engaging in them are obstacles that have left developing countries lagging behind, in terms of CSR (Meutia et al, 2017).…”
Section: Foreign Ownership and Firm Social Performancementioning
confidence: 99%
See 1 more Smart Citation
“…On the other, the CEO's experience from global affiliations opens the door to wider international connections that may help in receiving guidance and support to deal with the increasing societal pressure (Slater and Dixon-Fowler, 2009). Consistent with this logic, Meutia et al (2017) indicate that CEOs are more oriented to adopting familiar CSR practices virtue of their global working experience.…”
Section: Year-effect Controlledmentioning
confidence: 81%
“…A small number of existing studies devoted to emerging markets argue that the relationship between international aspects of corporate governance and CSR disclosure can be the opposite to that defined for developed countries (e.g. Amran and Devi, 2008;Khan et al, 2013;McGuinness et al, 2017;Meutia et al, 2017). These considerations indicate that the relevance of corporate governance characteristics and their contribution to CSR disclosure in emerging markets might differ from the relationships established in the mainstream of the literature devoted to developed markets, and that there is a need to understand the unique context of emerging markets (El Ghoul et al, 2016;Preuss and Barkemeyer, 2011;Alon et al, 2010;London and Hart, 2004;Maignan and Ralston, 2002).…”
Section: Introductionmentioning
confidence: 99%